PENERAPAN PEMBELAJARAN BERBASIS PROYEK TERHADAP PENINGKATAN KEMAMPUAN BERPIKIR KRITIS - Charles Fransiscus Ambarita; Febriana Krisdayanti Barus; Khairiah Khairiah; Dwi Susanti (CV. ADIBA ASIHA AMIRA, 2024)
This study aims to examine the impact of project-based learning planning on students' critical thinking skills. Using a quantitative research method with an experimental approach, this study involved high school students divided into an experimental group that applied project-based learning and a control group that used conventional learning methods. The results showed a significant improvement in critical thinking skills in the experimental group. These findings indicate that project-based learning can be an effective alternative for enhancing students' critical thinking skills.